Today Through the Lens of the Ancient Debate on the Value of Mētis - Slováček, Petr (Hybris, 2025)
In Today Through the Lens of the Ancient Debate on the Value of Mētis, the author examines contemporary challenges to freedom of speech in art, science, and politics through the ancient Greek concept of mētis—practical wisdom enabling success in life. He argues that mētis, rooted in the common sense of non-experts, faces suppression by those in power, termed the “anointed,” amid growing censorship and moralistic polarization. Drawing on Greek drama, particularly tragedies like Antigone and Prometheus Bound, the author highlights the role of mētis in exploring human complexity and fostering moral reflection, supported by insights from neuroscience and philosophy. The text contrasts mētis with hybris—excessive pride—illustrating how drama avoids simplistic judgments, promoting epistemic humility. The author connects these ideas to modern issues, suggesting that the erosion of liberal values and the marginalization of practical knowledge threaten individual agency. He concludes that mētis, alongside the moderation of sōphrosynē, offers a counterbalance to authoritarian tendencies. This interdisciplinary study underscores drama’s enduring relevance as a tool for understanding ethical dilemmas and resisting the overreach of power, urging a renewed appreciation for experiential wisdom in today’s world.